2021
DOI: 10.4235/agmr.21.0117
|View full text |Cite
|
Sign up to set email alerts
|

Association between Health Literacy, Self-care Behavior, and Blood Sugar Level among Older Patients with Type 2 Diabetes in Rural Thai Communities

Abstract: Background: Diabetes mellitus is a major problem worldwide. Moreover, older patients with significantly limited health literacy (HL) tend to have worse self-care behaviors and health outcomes. This study aimed to describe the associations of HL, self-care behavior, and blood sugar levels among older patients with type 2 diabetes in rural Thai communities.Methods: This cross-sectional study included 415 patients with diabetes who were purposively selected from rural Thai communities. Data were collected using q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…It was found in this study that about half of the participants wanted the state to provide them with support for their occupations and damaged equipment for the disabled. Similarly, prior studies have found that older adults' perception of the benefits of disability is important for them to access healthcare services, disease prevention materials, and health information during the COVID-19 pandemic [16,39], which might affect their health literacy [17,40] and QoL [29]. However, we conducted this study during the COVID-19 pandemic, which could have had an impact on the participants' access to health care and health insurance rights, lowering their QoL [41].…”
Section: Discussionmentioning
confidence: 86%
“…It was found in this study that about half of the participants wanted the state to provide them with support for their occupations and damaged equipment for the disabled. Similarly, prior studies have found that older adults' perception of the benefits of disability is important for them to access healthcare services, disease prevention materials, and health information during the COVID-19 pandemic [16,39], which might affect their health literacy [17,40] and QoL [29]. However, we conducted this study during the COVID-19 pandemic, which could have had an impact on the participants' access to health care and health insurance rights, lowering their QoL [41].…”
Section: Discussionmentioning
confidence: 86%
“…Tiller et al (2015) also found that health literacy was positively associated with education level, income level, and self-perceived social position. The literature also reported that health literacy demonstrated a significant relationship with age, education level, and income, and the health literacy level was found to be lower in individuals who were at an advanced age and who had low education and income level (Sabooteh et al, 2019;Suksatan et al, 2021). The higher education level of older individuals increased their health literacy scores.…”
Section: Discussionmentioning
confidence: 97%
“…Second, the moderated mediation model was tested with model 8 by age groups (young adults aged <40 and midlife adults aged ≥40) as moderators [ 34 ]. Education was treated as a controlled variable in the hypothetical model considering the influence of education on health literacy and self-care behavior [ 16 ]. The threshold of value of α was adjusted to less than 0.025, deviating from the conventional 0.05, aiming to mitigate the risk of Type I errors [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, health literacy has been theorized as one important, nonclinical factor that is associated with diabetes self-care behavior. The growing body of research has indicated that health literacy is a determinant of glycemic control [ 14 ], medication adherence [ 15 ], and diabetic control lifestyle adherence, such as blood glucose monitoring, foot care, and diet [ 16 ].…”
Section: Introductionmentioning
confidence: 99%